Uma análise do tema “Variação linguística” em aulas transmitidas pelo Centro de Mídias da Educação de São Paulo (CMSP) durante o período de Ensino Remoto Emergencial - Bernardo, Luziana Da Silva (Universidade Federal de São Carlos, 2025)
The main objective of this work is to analyze how linguistic variation was taught in classes transmitted by the Media Center (CMSP) to public schools in the state of São Paulo, during the period of emergency remote teaching (ERE), in order to verify whether the teachers adopted the theoretical-methodological perspective of Variationist and Educational Sociolinguistics regarding the teaching of linguistic variation and what was done with the students to awaken a sociolinguistic awareness. This research, with a qualitative approach and bibliographical-documentary type, is based on ideas originating in Educational Sociolinguistics (Bortoni-Ricardo, 2004, 2005; Bagno, 2007; Faraco, 2007, 2008; among other studies) and analyzes a corpus made up of class recordings from the São Paulo Education Media Center (CMSP). The research was carried out according to the following stages: 1. Bibliographic survey and literature review about teaching linguistic variation; 2. Corpus constitution (access to CMSP recordings and selection of a set of lessons broadcast during the ERE); 3. Transcription of some selected lessons; and 4. Analysis and discussion of the results. This study presents the analysis of the set of online lessons relating to the final years of elementary school II and secondary school. The analysis reveals that the ERE period could have been a good opportunity to work on developing students' sociolinguistic awareness, using various technological tools, such as videos, images, music, etc., considering that many schools do not have the structural conditions to do this in classroom teaching. However, despite these new possibilities, we found that the teaching of linguistic variation is still superficial, without much in-depth study of the factors that cause variation in the language; teaching is restricted to presenting the types of variation in a theoretical way, without showing students in a practical way how these variations occur. In addition, we found that the teachers had little knowledge of the use of technologies applied to teaching, which made those classes a reflection of what was already happening in public school classrooms, that is, a traditional methodology, focused on rules and the transmission of content. Clearly, the pandemic has passed and those recorded lessons will continue to be available on the internet. However, we hope that this study can contribute to improve the content made available on CMSP, and the training offered there for state school teachers, not just in São Paulo, but throughout Brazil. We also hope that the training offered will be of high quality, with the necessary topics and up-to-date materials, as well as encouraging teachers to read books, articles etc. on the subject of variation and teaching, the use of technologies and more dynamic methodologies than the traditional ones, allowing these topics to be explored in all their complexity and in full.
An analysis of the theme “Linguistic Variation” in classes broadcast by the São Paulo Education Media Center (CMSP) during the Emergency Remote Teaching period
Keywords: Ensino de variação linguística; Consciência sociolinguística; Ensino remoto emergencial; Centro de Mídias da Educação de São Paulo; Teaching linguistic variation; Sociolinguistic awareness; Emergency remote teaching; São Paulo Education Media Center; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA; LINGUISTICA, LETRAS E ARTES::ARTES